White Coat Hypertension, relationship of stages of hypertension with end organ damage and diurnal variation of blood pressure in newly diagnosed hypertensive patients - Paudel, Navaraj; Karki, Prahlad; Shreshta, Nikesh Raj; Sharma, Sanjib Kumar (Journal of Advances in Internal Medicine, 2012)
Introduction - Systemic hypertension is a disease attributable for various cardiovascular events. White coat hypertension is under diagnosed in Nepal and is usually treated as hypertension. However its prevalence in Nepal is not known. The relationship of stages of hypertension and diurnal variation of blood pressure with end organ damage is a current topic of research however such studies haven’t been done in Nepal. Methods - A Cross-sectional, Descriptive study including 80 patients was conducted over a period of 1 year from February 2008 to March 2010 at B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan. Results - The prevalence of white coat hypertension was 9%. Considering stage one (JNC 7) patients only it was 17%. There was statistically significant association between rise in blood pressure and proteinuria (p=<0.001). There was also significant relationship between the ECG and Fundoscopic changes with the rise in blood pressure (p value 0.003 and 0.041 respectively). There were 47% non-dippers, 44% dippers, 8% extreme dippers and 1% raisers with significant variations between active and resting blood pressure. Conclusion - The prevalence of White Coat Hypertension among stage one hypertensives was 17%. There is strong relationship between the rise in blood pressure and end organ damage. Majority of patients with pre?hypertension (JNC 7) showed micro-albuminuria. There was a significant variation between active and resting blood pressure. DOI: http://dx.doi.org/10.3126/jaim.v1i2.6504 Journal of Advances in Internal Medicine 2012;01(02):56-9